2019
DOI: 10.1080/13510002.2019.1596429
|View full text |Cite
|
Sign up to set email alerts
|

Early onset of renal oxidative stress in small for gestational age newborn pigs

Abstract: Objective: Oxidative stress, a common feature in cardiovascular and renal disease is associated with the causes and consequences of fetal growth restriction. Hence, renal redox status is likely an early determinant of morbidity in small-for-gestational-age (SGA) infants. In this study, we examined renal oxidative stress in naturally-farrowed SGA newborn pigs. Methods: We studied SGA newborn pigs with 52% less body weight and 59% higher brain/liver weight ratio compared with their appropriate-for-gestational-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 67 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…Newborns, because of their immature antioxidant capacity, are more prone to oxidative stress than adults [35,[63][64][65], leading to an increase in the risk factors that trigger in ammation, infection and ischemia and resulting in damage to multiple organs, which plays a key role in the pathogenesis of several perinatal diseases [66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Newborns, because of their immature antioxidant capacity, are more prone to oxidative stress than adults [35,[63][64][65], leading to an increase in the risk factors that trigger in ammation, infection and ischemia and resulting in damage to multiple organs, which plays a key role in the pathogenesis of several perinatal diseases [66][67][68].…”
Section: Discussionmentioning
confidence: 99%
“…Newborns, because of their immature antioxidant capacity, are more prone to oxidative stress than adults [35,[62][63][64], leading to an increase in the risk factors that trigger in ammation, infection and ischemia and resulting in damage to multiple organs, which plays a key role in the pathogenesis of several perinatal diseases [65][66][67].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that colostrum exosomes increased the secretion of factors related to Newborns, because of their immature antioxidant capacity, are more prone to oxidative stress than adults [35,[68][69][70], leading to an increase in the risk factors that trigger inflammation, infection and ischemia and resulting in damage to multiple organs, which plays a key role in the pathogenesis of several perinatal diseases [71][72][73].…”
Section: Exosomes Play a Key Role In Cell-to-cell Communication And Cmentioning
confidence: 94%